Battery Electric Vehicles in Underground Mining: Benefits, Challenges, and Safety Considerations - Epp Kuslap; Jiajie Li; Aibaota Talehatibieke; Michael Hitch (Energies, 2025)
This paper explores the implementation of battery electric vehicles (BEVs) in underground mining operations, focusing on their benefits, challenges, and safety considerations. The study examines the shift from traditional diesel-powered machinery to BEVs in response to increasing environmental concerns and stricter emission regulations. It discusses various lithium-ion battery chemistries used in BEVs, particularly lithium–iron–phosphate (LFP) and nickel–manganese–cobalt (NMC), comparing their performance, safety, and suitability for underground mining applications. The research highlights the significant benefits of BEVs, including reduced greenhouse gas emissions, improved air quality in confined spaces, and potential ventilation cost savings. However, it also addresses critical safety concerns, such as fire risks associated with lithium-ion batteries and the emission of toxic gases during thermal runaway events. The manuscript emphasises the importance of comprehensive risk assessment and mitigation strategies when introducing BEVs to underground mining environments. It concludes that while BEVs offer promising solutions for more sustainable and environmentally friendly mining operations, further research is needed to ensure their safe integration into underground mining practices. This study contributes valuable insights to the ongoing discussion on the future of mining technology and its environmental impact.